The technology behind the tennis at Wimbledon - Foreman, S. (Sports Performance & Tech, 2015)
Wimbledon is the most prestigious tennis tournament in the world. One billion people tuned in over the course of the two-week event this year, but the All England Lawn Tennis Club (AELTC) doesn`t rest in its quest to drive engagement and promote its product around the world. They look to provide broadcasters, players and coaches with as many stats as possible to enhance the Wimbledon brand. Sean Foreman investigates the use of technology that helps the most famous tennis tournament in the world run every year.